2015
DOI: 10.1016/j.ahj.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Associations of obesity and body fat distribution with incident atrial fibrillation in the biracial health aging and body composition cohort of older adults

Abstract: Introduction Obesity is a well-recognized risk factor for atrial fibrillation (AF) yet adiposity measures other than body mass index (BMI) have had limited assessment in relation to AF risk. We examined the associations of adiposity measures with AF in a biracial cohort of older adults. Given established racial differences in obesity and AF, we assessed for differences by black and white race in relating adiposity and AF. Methods We analyzed data from 2,717 participants of the Health, Aging, and Body Composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
2
24
0
1
Order By: Relevance
“…In further subgroup analyses of two studies that reported data stratified by ethnicity [31, 37], the summary RR per 5 BMI units was 1.14 (95% CI: 1.06–1.22) among Caucasians and 1.23 (95% CI: 1.09–1.39) for African Americans, with no significant heterogeneity between subgroups, p  = 0.39. When the studies of BMI and atrial fibrillation were stratified by study design, the summary RR was 1.15 (95% CI: 0.67–1.98, I 2  = 69.5%) for the nested case–control studies and 1.30 (95% CI: 1.23–1.38, I 2  = 94.3%) for the cohort studies.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In further subgroup analyses of two studies that reported data stratified by ethnicity [31, 37], the summary RR per 5 BMI units was 1.14 (95% CI: 1.06–1.22) among Caucasians and 1.23 (95% CI: 1.09–1.39) for African Americans, with no significant heterogeneity between subgroups, p  = 0.39. When the studies of BMI and atrial fibrillation were stratified by study design, the summary RR was 1.15 (95% CI: 0.67–1.98, I 2  = 69.5%) for the nested case–control studies and 1.30 (95% CI: 1.23–1.38, I 2  = 94.3%) for the cohort studies.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, it is not clear whether other measures of body fatness such as waist circumference [26, 2932], hip circumference [30, 32, 33], waist-to-hip ratio [29, 30, 32, 33], fat mass [3032, 34], or body fat percentage [30, 31, 34] are associated with risk of atrial fibrillation or if the association differs by geographic location or ethnicity. Although a meta-analysis from 2008 found that both overweight and obesity as measured by body mass index (BMI) was associated with increased risk of atrial fibrillation [35], at least 20 additional studies involving >78,000 atrial fibrillation cases and >2.2 million participants have been published since that meta-analysis [20, 21, 2331, 33, 34, 3642]. Given the large number of additional studies that have been published since the previous meta-analysis and the availability of data regarding other adiposity measures as well, we conducted a systematic review and dose–response meta-analysis of prospective studies that investigated the association between body mass index, waist circumference, waist-to-hip ratio, or other measures of adiposity (hip circumference, fat mass, weight, weight gain) and the risk of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the current study suggest that abdominal obesity is positively associated with AF risk in Asian persons; however, a nonlinear J‐shaped association was found between continuous BMI variables and AF risk—AF risk positively increased with the increase of WC. Aronis et al reported that BMI, abdominal circumference, and total fat mass are associated with risk of AF among white and black older adults 40. The LEGACY study demonstrated the beneficial effects of long‐term sustained weight loss and participation in a tailored exercise program on reducing AF recurrence in obese persons 41.…”
Section: Discussionmentioning
confidence: 98%
“…The LEGACY study demonstrated the beneficial effects of long‐term sustained weight loss and participation in a tailored exercise program on reducing AF recurrence in obese persons 41. Obesity reduction can modify the incidence of AF 40. Nevertheless, there are limited data assessing the association between risk of AF and abdominal obesity in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Upon reaching a critical mass, the remodeled left atrium becomes more susceptible to initiating and sustaining AF. This is evidenced by obese individuals having increased heterogeneity in atrial refractoriness [7] and enhanced sympathetic cardiac innervation, both of which render the atrial tissue more vulnerable to AF [8][9][10].…”
mentioning
confidence: 99%